Attitudes Toward Lesbians and Gay Men Scale: validation in Brazilian physicians - Corrêa-Ribeiro,Renata (2019)
ABSTRACT Objective: To perform the cross-cultural adaptation of the original North American version of the Attitudes Toward Lesbians and Gay Men Scale (ATLG) for use in Brazil, and to evaluate the psychometric properties of the adapted instrument in a sample of Brazilian heterosexual physicians. Methods: Stages of cross-cultural adaptation were as follows: translation by two independent evaluators, translation synthesis, evaluation by the target population for semantic equivalence, pilot study with 42 physicians, and final instrument preparation involving 224 heterosexual physicians practicing medicine in the Federal District. Invitations containing a link to the study were sent to physicians via e-mail, social media and medical associations. Inclusion criteria were as follows: being a physician authorized to practice medicine in Brazil, practicing medicine in the Brazilian Federal District, and self-declared heterosexual, as stipulated in the original version of the ATLG scale. Exclusion criteria were not disclosed to potential participants to avoid inhibition and unwillingness to participate; respondents meeting exclusion criteria were removed from the sample during data analysis. Results: Exploratory and confirmatory factor analyses suggested a one-factor solution to be the most representative of the data, including all 20 items with high reliability (composite reliability coefficients =0.948). Conclusion: The ATLG scale is a suitable instrument to assess physicians’ attitudes toward homosexuals, with good validity and reliability evidence based on the sample studied.